2015
DOI: 10.1002/nau.22913
|View full text |Cite
|
Sign up to set email alerts
|

Continuous urethral pressure measurements; measurement techniques; pressure variations; clinical interpretations; and clinical relevance. A Systematic Literature Analysis

Abstract: There exists a phenomenon of UPV, apart from DO, which may be a separate entity within OAB syndrome. Large variation in measurement techniques and patient populations hinders fundamental research as well as clinical progress. Clinical relevance of UPV and consequences for treatment therefore are yet to be established. Future prospective research with well-defined patient population and standardised urodynamic measurement techniques is needed. Results of standardized and objective evaluations should be compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…10 In addition, studies have shown that the effects of the beta-3-agonist, mirabegron on urethral smooth muscle are the result of β3-AR agonism together with α1A/α1D-AR antagonism. 11 Electrophysiological studies in anesthetized rats have demonstrated the presence of urethral distension evoked afferents in the pelvic and pudendal nerves. 12 Interstitial cells (ICs) in the urethra have, in analogy with these in the intestine, the interstitial cells of Cajal (ICC), been proposed as specialized pacemakers that are involved in the generation of urethral tone.…”
Section: Urethra Sensory and Autonomic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, studies have shown that the effects of the beta-3-agonist, mirabegron on urethral smooth muscle are the result of β3-AR agonism together with α1A/α1D-AR antagonism. 11 Electrophysiological studies in anesthetized rats have demonstrated the presence of urethral distension evoked afferents in the pelvic and pudendal nerves. 12 Interstitial cells (ICs) in the urethra have, in analogy with these in the intestine, the interstitial cells of Cajal (ICC), been proposed as specialized pacemakers that are involved in the generation of urethral tone.…”
Section: Urethra Sensory and Autonomic Dysfunctionmentioning
confidence: 99%
“…Bladder pain syndrome and OAB appear to share some common pathophysiology including increased purinergic, TRPV1, and muscarinic signalling, increased urothelial permeability, and aberrant urothelial differentiation . In addition, studies have shown that the effects of the beta‐3‐agonist, mirabegron on urethral smooth muscle are the result of β3‐AR agonism together with α1A/α1D‐AR antagonism . Electrophysiological studies in anesthetized rats have demonstrated the presence of urethral distension evoked afferents in the pelvic and pudendal nerves …”
Section: What Do We Know From Research and From Normal Physiology Andmentioning
confidence: 99%
“…This definition was abandoned shortly after because this is a rare phenomenon. In a recent review, it was concluded that studies on this subject have diversity in measurement techniques and materials . Urodynamic catheters with the variation of one to six sensors in the urethra have been used in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, it was concluded that studies on this subject have diversity in measurement techniques and materials. 5 Urodynamic catheters with the variation of one to six sensors in the urethra have been used in the literature. [6][7][8][9] In the studies performed with multiple urethral pressure sensors, all sensors registered the UPV simultaneously, they have, however, been best recognized at the point of maximal urethral pressure.…”
Section: Introductionmentioning
confidence: 99%
“…4 In a recent review was concluded that despite the poor methodological quality of the performed studies UPV may be regarded a -potentially pathophysiological entity of its own within cohorts of patients with OAB. 5 anticholinergics or beta-3 receptor agonists, pudendal or sacral nerve stimulation and intravesical Botulinum toxin-A (BoNT-A) therapy. 6 In the past, surgical bladder denervation has been performed as treatment modality for OAB.…”
Section: Introductionmentioning
confidence: 99%